Multi-level issues in organizational behavior and strategy - Dansereau, Fred, 1946-; Yammarino, Francis J., 1954- (Emerald, 2003)
Using a scientific debate format of a key scholarly essay followed by two commentaries and a rebuttal, this series presents theoretical work, significant empirical studies, methodological developments, analytical techniques, and philosophical treatments to advance the field of multi-level studies, regardless of disciplinary perspective. Similar to Volume 1 (Yammarino & Dansereau, 2002), Volume 2 contains five major essays that cover a range of topics, but in the realms of organizational behavior and strategy. In particular, the five critical essays offer extensive literature reviews, new model developments, methodological advancements, and some empirical data for the study of emotions, construct validation, firm performance, interfirm networks, and strategic change. While each of the major essays, as well as the commentaries and rebuttals, is unique in orientation, they share a common bond in raising and addressing multi-level issues, or discussing problems and solutions that involve multiple levels of analysis.
Keywords: Organizational behavior.; Strategic planning.; Personnel management.; elektronické knihy; electronic books